Insurgent visions : feminism, justice, solidarity / Chandra Talpade Mohanty. - Mohanty, Chandra Talpade, 1955- (Duke University Press, 2025)
In a current era marked by carceral logics, authoritarianism and white supremacy, there has never been a greater need for the tools and inspiration that radical feminism provides. In 'Insurgent Visions', Chandra Talpade Mohanty explores methods of anticapitalist resistance to radically transform everyday life. She presents insurgent feminism - a theory and praxis with which to contest and replace the practices of violence grounded in racialized gender relations.